The antioxidant effect of ubiquinone and combined therapy on mitochondrial function in blood cells in non-proliferative diabetic retinopathy: A randomized, double-blind, phase IIa, placebo-controlled study - Adolfo Daniel Rodríguez-Carrizalez; José Alberto Castellanos-González; Esaú César Martínez-Romero; Guillermo Miller-Arrevillaga; Luis Miguel Román-Pintos; Fermín Paul Pacheco-Moisés; Alejandra Guillermina Miranda-Díaz (Redox Report, 2016)
Objectives: To evaluate the effect of ubiquinone and combined antioxidant therapy on mitochondrial function in non-proliferative diabetic retinopathy (NPDR) in a randomized, double-blind, phase IIa, placebo-controlled, clinical trial. Three groups of 20 patients were formed: Group 1, ubiquinone; Group 2, combined therapy; and Group 3, placebo (one daily dose for 6 months).Methods: Fluidity of the submitochondrial membrane in platelets was determined by examining intensity of fluorescence between the monomer (Im) and excimer (Ie). Hydrolytic activity of the mitochondrial F0F1-ATPase was evaluated with the spectrophotometric method.Results: Normal, baseline submitochondrial membrane fluidity, 0.24 ± 0.01 Ie/Im, was significantly diminished in the three study groups vs. normal values (P < 0.0001); placebo, 0.14 ± 0.01 Ie/Im; ubiquinone, 0.14 ± 0.01 Ie/Im; and combined therapy, 0.13 ± 0.00 Ie/Im. Afterward, it increased significantly (P < 0.0001), the ubiquinone group 0.22 ± 0.01 Ie/Im, combined therapy group, 0.19 ± 0.01 Ie/Im; with no changes the placebo group. Baseline hydrolytic activity of the F0F1-ATPase enzyme increased in the three study groups vs. normal values (184.50 ± 7.84 nmol PO4), placebo, 304.12 ± 22.83 nmol PO4 (P < 0.002); ubiquinone, 312.41 ± 25.63 nmol PO4 (P < 0.009); and combined therapy, 371.28 ± 33.50 nmol PO4 (P < 0.002). Afterward, a significant decrease the enzymatic activity: ubiquinone, 213.25 ± 14.19 nmol PO4 (P < 0.001); and combined therapy, 225.55 ± 14.48 nmol PO4 (P < 0.0001).Discussion: Mitochondrial dysfunction significantly improved in groups of NPDR patients treated with antioxidants.